Evaluation and Comparison of Sulfate Anions Removal from Artificial and Industrial Wastewaters by Nanofiltration Process in a Laboratory Scale - Hangi, Ali; Mohebbi, Ali; Mirzaei, Mohammad; Kaydani, Hossein (Journal of Membrane and Separation Technology, 2015)
In this study, the performance of a nanofiltration process in sulfate anion reduction from artificial and industrial wastewaters was investigated. For this purpose, the effects of pressure, temperature, and volume flow rate and sulfate concentration of feed were studied. In order to prepare artificial wastewater (i.e. Sodium Sulfate) and to adjust the pH of the feed, both Sodium Hydroxide and Acetic Acid were used. The concentration of sulfate in the artificial wastewater was in the range of the industrial one (i.e. 400 500 ppm) and the pressure range, which had the most important influence on retention, was between 138 552kPa. In order to organize the experiments and obtain a specific procedure to perform the required tests, Minintab 16 software has been utilizes. The results showed that the reduction of sulfate anions, which had bivalent charge with big molecule size, occurred at high level of 96 99%. Higher pressure and temperature led to increase in this retention rate, while it reduced at high level of sulfate concentration in the feed. The condition in which the pressure, temperature, and feed flow rate were respectively 50345 kPa, 25ºCand 4L/min were indicated as the optimum condition.